Post-cold war security in Europe: from collective defense back to collective security - Türksever, Fehmi (My University, 2003)
SOĞUK SAVAŞ SONRASI AVRUPA'DA GÜVENLİK: KOLEKTİF SAVUNMADAN KOLEKTİF GÜVENLİĞE Soğuk Savaş'ın bitmesiyle Avrupa-Atlantik bölgesine yeni bir güvenlik yapısı ortaya çıkmış ve kuzey yarımkürede yeni anlayışlara neden olmuştur. Büyük ve hızlı değişimler Soğuk Savaş yıllarındaki hareketsizliğe son vermiş ve Avrupa'da güvenliğin daha geniş bir zemine kaymasına neden olmuştur. Güvenliğin kapsamı genişleyerek bir ülke ya da ittifakın toprak bütünlüğünden daha fazla anlam taşımaya başlamıştır. Artık ana amaç hukuk kuralları, özgürlük ve serbestlik gibi ortak ve kabul gören normların, değerlerin korunmasıdır. Soğuk Savaş sonrasında, tüm kurumlar yeni güvenlik ortamına uyumlarını sağlayabilmek için güvenlik stratejilerinin temel unsurlarını ve önceliklerini yeniden değerlendirmeye çalışmaktadırlar. Soğuk Savaş'ın bitişi ile, NATO kendisini kollektif savunma düzeninden kollektif güvenlik düzenine doğru dönüştürmüştür. Bu çerçevede Stratejik Konseptini yenilemiş, yapısını esnek CJTFler ile değiştirmiş, eski düşmanlarıyla işbirliğini arttırmaya çalışmış ve Soğuk Savaş sonrası ilk genişlemeyi gerçekleştirmiştir. Diğer taraftan, Maastricht Anlaşması'ndan beri, AB ülkeleri AB'nin gelişen entegrasyon sürecindeki eksiklikleri gidermek üzere ortak bir güvenlik ve savunma politikası oluşturmaya çalışmaktadırlar. NATO içerisinde kalarak ayrılabilen fakat ayrı olmayan bir Avrupa kuvveti oluşturmaya dönük başlangıç çabaları, AB çerçevesinde otonom bir Avrupa Güvenlik ve Savunma Politikası oluşturmanın yolunu açmıştır. Bununla birlikte atılan bu adımlara rağmen günümüzün karmaşık güvenlik ortamında yaşayabilir, muktedir ve otonom bir Avrupa güvenlik yapısı oluşturmak zordur.

POST COLD WAR SECURITY IN EUROPE: FROM COLLECTIVE DEFENSE BACK TO COLLECTIVE SECURITY Since the end of the Cold War, new security environment emerged in Euro-Atlantic region and created new insights over the northern hemisphere. The dramatic, rapid and profound changes in the Europe put an end to Cold War deadlock and caused the security arrangements in Europe transformed into a broader domain. Security has become much broader in scope and comprises more than the territorial integrity of a nation, or an Alliance. Its main goal is to keep common and accepted norms and values, like the rule of law, freedom and liberty, undamaged. In the post-Cold War era, all institutions tried to reassess their priorities and the fundamental elements of their security strategies in order to adapt themselves to the new environment. With the end of Cold War, the NATO has transformed itself from a collective defense arrangement towards a collective security. It changed the its Strategic Concept, rearranged its structure with CJTFs, increased the cooperation with former allies through PfP and EPAC, and carried out the first enlargement round in the post-Cold War era. On the other hand, since the Maastricht Treaty, the European Union countries have been trying to form a common security and defense policy to fulfill the gaps in the evolutionary process of European Union unification. The initial efforts to create separable but not separate European forces within NATO have paved the way for creating an autonomous European Security and Defense Policy within the framework of the EU. However, despite these ambitious steps, it is very difficult to create a viable, capable and autonomous European security structure in today's complex security environment
Keywords: Güvenlik_Avrupa; Soğuk Savaş_Avrupa Birliği